Complex, Intelligent and Software Intensive Systems : Proceedings of the 14th International Conference on Complex, Intelligent and Software Intensive Systems (CISIS-2020) /: Proceedings of the 14th International Conference on Complex, Intelligent and Software Intensive Systems (CISIS-2020). (2020) - Unknown
No abstract available